1993
DOI: 10.1038/362458a0
|View full text |Cite
|
Sign up to set email alerts
|

Infection of natural killer cells by human herpesvirus 6

Abstract: Natural killer (NK) cells are a functionally defined subset of non-T, non-B lymphocytes of bone marrow origin, which induce lysis of selected target cells, including neoplastic and virus-infected cells. The NK cell function provides an important mechanism of primary defence against viruses in vivo, as demonstrated by the occurrence of multiple herpesvirus infections in patients congenitally lacking NK cells. Here we show that functionally competent CD3- NK clones can be productively infected by human herpesvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
121
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 27 publications
5
121
0
2
Order By: Relevance
“…HHV-6, by using CD46 as a cellular receptor, 51 has tropism for CD4 T lymphocytes, and it also interacts with other cells of the immune system such as natural killer cells and CD8 T lymphocytes; such interaction with the immune system results in decreased interleukin-2 levels and enhanced susceptibility to apoptosis. 48,52,53 HHV-7 uses CD4 as the cellular receptor to infect T cells. 54 The role of virus-induced immunomodulation as the sole or primary predictor of increased opportunistic infections has, however, been confounded by the iatrogenic pharmacologic immunomodulation that is inherent during the posttransplantation period.…”
Section: Indirect Effectsmentioning
confidence: 99%
“…HHV-6, by using CD46 as a cellular receptor, 51 has tropism for CD4 T lymphocytes, and it also interacts with other cells of the immune system such as natural killer cells and CD8 T lymphocytes; such interaction with the immune system results in decreased interleukin-2 levels and enhanced susceptibility to apoptosis. 48,52,53 HHV-7 uses CD4 as the cellular receptor to infect T cells. 54 The role of virus-induced immunomodulation as the sole or primary predictor of increased opportunistic infections has, however, been confounded by the iatrogenic pharmacologic immunomodulation that is inherent during the posttransplantation period.…”
Section: Indirect Effectsmentioning
confidence: 99%
“…[11][12][13][14][15] In the present report, we describe two cases of immunocompetent adults who presented with fever and generalized lymphadenopathy, and on biopsy were found to have viral lymphadenitis with massive numbers of viral inclusions in CD4-positive T lymphocytes. The presence of the virus in these cells was confirmed by immunohistochemistry, and electron microscopy and molecular studies identified distinctive features of HHV-6B.…”
mentioning
confidence: 99%
“…One particular aspect of HHV-6 pathogenesis is its ability to infect cell types of hematopoietic origin. HHV-6 can infect T cells (7), B cells (1), NK cells (8), megakaryocytes (9), and monocytes/macrophages (10,11). It is also suggested that HHV-6 can establish a latent infection in the monocyte/macrophage lineage (10).…”
mentioning
confidence: 99%